The student voice as contributor to quality education through institutional design - Strydom, F.; Loots, S. (South African Journal of Higher Education, 2020)
The inclusion of students’ voices in different aspects of quality has evolved over the years. Consequently, students take on different roles – ranging from providing feedback on their educational experiences, to actively participating or even leading change initiatives. In making claims for different ways of conceptualising or including students’ voices, the literature often criticises some forms of engagement with student voices in favour of another. This article is based on the premise that the complexity of quality outcomes in higher education needs to be complemented by a variety of inputs from students. By drawing from examples of two high-impact practices from the University of the Free State, the article further argues for using different forms of student voices to inform how we design institutional support structures to ultimately enhance the quality of students’ educational experiences. At its core, this cyclical interaction between students’ voices and institutional design revolves around evidence – thereby contributing to the quality of educational outcomes, and ultimately students’ success.